Structural and Spectroscopic Properties of Two New Isostructural Complexes of Lapacholate with Cobalt and Copper - Farfán, R. A. (2012)
The molecular structures of two isostructural complexes of lapacholate (Lap) anion and dimethylformamide (DMF), M(Lap)2(DMF)2 with M: Co Cu, were determined by X-ray diffraction methods. The substances crystallize in the triclinic space group P1 with one molecule per unit cell and cell constants a = 7.7591(3), b = 10.3560(3), c = 11.2224(4) A, α = 95.110(2), β = 94.310(2), and γ = 107.704(2)◦ for the Co complex and a = 7.9308(2), b = 10.0033(4), c = 10.7508(4), α = 97.387(2), β = 93.621(2), and γ = 103.980(2)◦ for the Cu complex. The structures were solved from 2933 (Co) and 2888 (Cu) reflections with I > 2σ (I) and refined by full matrix least squares to agreement R1-factors of 0.041 (Co) and 0.033 (Cu). The metal M(II) ion is sited on a crystallographic inversion center in a MO6 distorted octahedral environment. This ion is coordinated equatorially to two lapacholate anions through their adjacent carbonyl and phenol oxygen atoms [M–O bond distances of 2.134(1) and 2.008(1) A˚ (Co) and 2.301(1) and 1.914(1) A (Cu)] and axially to two DMF molecules through oxygen atoms [M–O bond lengths of 2.143(1) ˚ A (Co) and 2.069(1) ˚ A (Cu)]. The solid state IR transmittance and solution electronic absorption spectra of both Co and Cu ˚ compounds are also reported and compared to each other and to the corresponding spectra of other members of the lapacholate metal family of complexes.